The influence of the use of brand ambassador ‘stray kids’ in Shopee 12.12 birthday sale advertisement and Shopee’s brand image towards brand loyalty - Sri Nur Astika; Sylvie Nurfebiaraning (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
Consumers may decide to use product or service based on people who influence them. Consumers more likely to choose and be loyal to good brand they already trust rather than trying a new brand. Brand loyalty owned by the company aims to increase brand value by maintaining consumers not to switch to other brands. This research aims to determine how much influence Stray Kids brand ambassadors and Shopee’s brand image towards Shopee’s brand loyalty. This research used quantitative methods with causal type. The sampling technique in this study used non-probability sampling type purposive sampling. The sample used as many as 166 respondents from the population with an unknown size of Shopee users among Stray Kids fans. Data analysis used in this study includes correlation coefficients, multiple linear regression tests, T-tests, F tests, and determination coefficients. The results showed that brand ambassador 'Stray Kids' had a positive and significant influence on Brand Loyalty, with an increase of 0.118. Shopee’s brand image has a positive and significant influence on Brand Loyalty with an increase of 0.553. 'Stray Kids' brand ambassador and Shopee brand image simultaneously influence brand loyalty by 57.9%. The remaining 42.1% were influenced by factors not discussed in the study.